California Democratic Council Statewide Convention at Hacienda Inn - Watkins, Howard::::::::: (1982)
Fresno Mayor Dan Whitehust welcoming everyone; head table; delegates from districts 22, 21, 17, and 3 Convention Banner: We the people action for the '80's"